ANTITUMOR ACTIVITY, HEMATOXICITY AND HEPATOTOXICITY OF SORAFENIB FORMULATED IN A NANOEMULSION BASED ON THE CARROT SEED OIL: Pharmaceutical Sciences-Nanotechnology - H. ALKHATIB, MAYSON; S. ALNAHDI, NUJUD; S. BACKER , WADIAH (International Journal of Life Science and Pharma Research, 2022)
Combining the chemotherapeutic agent, sorafenib (SRF), with the essential oil, carrot seed oil, can help in reducing the adverse side effects of the SRF. However, the different solubilities of both components impede the mixing, which can be overcome by formulating the carrot oil in a nanoemulsion (NANO). The aim of the present study was to evaluate the anticancer activity, hematoxicity and hepatoxicity of SRF when mixed with the nanoemulsion formulated of the carrot oil (NANO-SRF). As measured by the zetasizer, it has been found that the dispersed nanodroplets of the formulated NANO and NANO-SRF have z-average diameters of 10.27 ± 2.39 nm and 68.92 ± 10.6nm, respectively. Forty female Swiss Albino mice bearing Ehrlich ascites carcinoma (EAC) were split into four groups (n =10). Group I served as the untreated EAC mice while groups II-IV were administered via oral gavage with the 30 mg/kg mouse of SRF solubilized in 0.2 mL of Chremophore/ethanol solution, 30 mg/kg mouse of SRF solubilized in 0.2 mL of NANO and 0.2mL of drug –free NANO, respectively. The results of the antitumor assessment revealed that the GPX and LDH activities in the ascetic fluid of III-NANO-SRF group were enhanced when compared to II-SRF group. The white blood cell counts reduced while the number of the platelets increased for III-NANO-SRF group when compared to II-SRF group. The amounts of alanine aminotransferase (ALT), alkaline phosphatase (ALP), total bilirubin (T.BIL) and direct bilirubin (D. BIL) of the mice treated with the NANO-SRF were ameliorated when compared to the mice treated with the SRF formula. Mixing the SRF with the NANO has improved the efficacy of SRF while reducing its hematoxicity and hepatotoxicity.